Youth Participatory Approaches and Health Equity: Conceptualization and Integrative Review. Issue 3 (24th September 2020) - Ozer, Emily J.; Abraczinskas, Michelle; Duarte, Catherine; Mathur, Ruchika; Ballard, Parissa Jahromi; Gibbs, Lisa; Olivas, Elijah T.; Bewa, Marlene Joannie; Afifi, Rima
Abstract: There is an array of youth participatory approaches relevant to health equity efforts in community psychology, adolescent health, youth development, and education. While they share some commonalities, they also reflect important distinctions regarding key processes and intended level of impact. Here, we consider the following: (a) youth‐led participatory action research (YPAR), (b) youth organizing (YO), (c) youth‐led planning, (d) human‐centered design, (e) participatory arts, and (f) youth advisory boards. Informed by community psychology theories on empowerment and levels of change and social epidemiology frameworks that focus on the social determinants of health inequities, we aim to promote greater clarity in the conceptualization, implementation, and evaluation of youth participatory approaches; frame the "landscape" of youth participatory approaches and their similarities and differences; present an integrative review of the evidence regarding the impact of youth participatory approaches; and describe several illustrative cases so as to consider more deeply how some youth participatory approaches aim to influence the social determinants of health that lead to the physical embodiment of health inequities. We conclude by identifying areas of future policy‐ and practice‐relevant research for advancing youth participation and health equity. Highlights: We review multiple youth participatory approaches relevant for the promotion of health equity. We identify commonalities and distinctions on processes including power and level of impact. We review evidence for impact and consider illustrative cases for addressing health inequities. We identify research directions for advancing youth participation and health equity.